2008
DOI: 10.1212/01.wnl.0000313857.54398.0e
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of decreased CSF asialotransferrin for eIF2B-related disorder

Abstract: Objective-This is a study estimating diagnostic accuracy of CSF asialotransferrin to transferrin ratio measurement in eIF2B related disorders by using clinical evaluation and EIF2B mutation analysis as the reference standard. eIF2B-related disorder is a relatively common leukodystrophy with broad phenotypic variation that is caused by mutations in any of the five EIF2B genes. There is a need for a simple and clinically valid screening tool for physicians evaluating patients with an unclassified leukodystrophy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Actually, detection of asialo-Tf in the blood may be an indication of carbohydrate deficient glycoprotein syndrome often associated with alcohol abuse [12] or other congenital disorders of glycosylation known as CDG disorders [5, 13]. Inversely, absence of asialo-Tf in the CSF is abnormal and could indicate a serious neurological disorder, as we have previously demonstrated in patients with Vanishing White Matter (VWM) disease, a type of leukodystrophy characterized by deterioration of the white matter in the brain [14, 15]. The exact role of asialo-transferrin in the central nervous system is not well understood at present but it represents up to 30% of total circulating Tf in the CSF.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, detection of asialo-Tf in the blood may be an indication of carbohydrate deficient glycoprotein syndrome often associated with alcohol abuse [12] or other congenital disorders of glycosylation known as CDG disorders [5, 13]. Inversely, absence of asialo-Tf in the CSF is abnormal and could indicate a serious neurological disorder, as we have previously demonstrated in patients with Vanishing White Matter (VWM) disease, a type of leukodystrophy characterized by deterioration of the white matter in the brain [14, 15]. The exact role of asialo-transferrin in the central nervous system is not well understood at present but it represents up to 30% of total circulating Tf in the CSF.…”
Section: Introductionmentioning
confidence: 99%
“…through nose and ears), but there are not studies of this clinical application by MS so far. However, Vanderver et al [94] reported a deficiency of S 0 in CSF from patients with childhood-onset ataxia and central hypomyelination (CACH) using MALDI-TOF/TOF MS and Nanospray FT-MS measurements. This finding opens to the use of S 0 as a potential clinical diagnostic biomarker.…”
Section: Transferrin Sialoformsmentioning
confidence: 99%
“…Instructive examples are those of sepsis and/or acute pancreatitis [3,4], myocardial infarction [5,6], ANCA-associated systemic vasculitis [7], Alzheimer [8,9], Parkinson [10], childhood-onset ataxia and central nervous system hypo-myelination (CACH/VWM) disease [11], alcohol abuse [12] and glycosyl-transferases dysfunctions [13].…”
Section: Introductionmentioning
confidence: 99%